Heat transfer model of slurry ice melting on external surface of helical coil - Thongwik S. (2014)
This research studies the heat transfer phenomenon of melting slurry ice on external surface of a copper helical coil. There is water flowing inside the tube coil and exchanging heat with the slurry ice. In this experiment, the coil diameters are 6.35 mm and 9.53 mm each of 4.2 m coil length. The mass flow rate of water in the helical coil is between 0.0149-0.0562 kg/s, while the inlet temperature of water is varied in the range of 23-27 °C. The slurry ice has 60% ice and 40% water by mass at the starting. The experimental results show that, with small coil diameter, high mass flow rate of circulating water and low ice fraction, high heat transfer coefficient of the slurry ice at the warm helical coil surface is obtained. The heat transfer models of slurry ice during melting and post-melting in terms of Nusselt number with the pertinent parameters are also developed. The results agree very well with the experimental data. © 2008 Elsevier Ltd. All rights reserved.